Knowledge, Attitude and Practices Regarding Antibiotics usages among Medical Students at Zawia University - Reemah Almadah; Hana Alazraq; Mufida Khetresh; Shahrazad Gazeti (AlQalam Journal of Medical and Applied Sciences, 2024)
Antimicrobial resistance (AMR) is a serious threat to global public health. It increases morbidity and mortality, and is associated with high economic costs due to its health care burden. Medical students are particularly important since they will be the future leaders in clinic practice, responsible for antibiotic prescription and communication about antibiotic use with their patients. In this study we aimed to understand knowledge, attitude, and practice (KAP) with respect to antibiotic use among medical students in faculty of medicine, Zawia University. This is a cross-sectional design; it was undertaken in Faculty of Medicine during October and November: 2023. The questionnaire was administered to students in (III 3rd and IV 4th grades). All data were analyzed using Statistical Package for Minitab program. Majority of the respondents were female with ages of 22 years. Higher percentage of 4th-grade students (95.5%) correctly accepting the need to stop antibiotic use compared to 3rd-grade students (27.9%, p < 0.001). On other hand with a higher percentage of 4th-grade students reporting using non-prescribed antibiotics rarely compared to 3rd-grade students (46.3% for 4th grade and 69.8% for 3rd grade, p = 0.003). this study exposed an important awareness concerning the separate between medical students’ knowledge about antimicrobial resistance, and appalling attitudes and practices towards antibiotics use. We need for the re-evaluation of the educational curricula especially, teaching of clinical pharmacology courses in clinical years. تعد مقاومة المضادات الحيوية تهديداً كبيراً للصحة العامة على مستوى العالم، حيث تؤدي إلى زيادة في معدلات الإصابة بالأمراض والوفيات، كما أنها تفرض تكاليف اقتصادية مرتفعة نتيجة الأعباء التي تلقيها على أنظمة الرعاية الصحية. يلعب طلاب الطب دوراً حيوياً في مواجهة هذا التحدي، إذ سيكونون مستقبلاً المسؤولين عن وصف المضادات الحيوية والتوعية باستخدامها لدى المرضى. هدفت هذه الدراسة إلى تقييم مستوى المعرفة والمواقف والممارسات المتعلقة باستخدام المضادات الحيوية بين طلاب كلية الطب بجامعة الزاوية. تم استخدام تصميم مقطعي لإجراء الدراسة، والتي تم تنفيذها في شهري أكتوبر ونوفمبر 2023. شملت الدراسة توزيع استبيان على طلاب الصفين الثالث والرابع في الكلية. تم تحليل البيانات باستخدام برنامج "Minitab" الإحصائي. أظهرت النتائج أن غالبية المشاركين من الإناث، بمتوسط عمر 22 عاماً. وأفاد 95.5% من طلاب السنة الرابعة بأنهم يتفقون على ضرورة التوقف عن استخدام المضادات الحيوية عند الحاجة، مقارنة بنسبة 27.9% من طلاب السنة الثالثة (p < 0.001). بالإضافة إلى ذلك، أفاد طلاب السنة الرابعة بأنهم نادراً ما يستخدمون المضادات الحيوية دون وصفة طبية بنسبة 46.3%، مقارنة بنسبة 69.8% بين طلاب السنة الثالثة (p = 0.003).كشفت الدراسة عن فجوة واضحة بين معرفة طلاب الطب بمشكلة مقاومة المضادات الحيوية، وبين مواقفهم وممارساتهم الفعلية تجاه استخدامها. وتبرز الحاجة إلى إعادة تقييم المناهج الدراسية، خاصة فيما يتعلق بتدريس علم الأدوية السريري خلال السنوات السريرية